2312. Mortality of Severe Dengue Patients Admitted to Intensive Care Units over 15 Years: Have We Improved? - Rosso, Fernando (Open Forum Infect Dis, 2019)
BACKGROUND: Dengue mortality can be preventable in endemic regions. However, access to intensive care units (ICU) and continuous monitoring strategies are limited in developing countries. In 2010, WHO dengue clinical practice guidelines (CPG) were implemented in the Americas region which strengthened hospital healthcare management and prioritized early ICU admission in severe dengue cases. We hypothesized that early access to the ICU might decrease the mortality of patients with dengue. This study aimed to describe trends in dengue cases and mortality in the ICU for 15 years in Cali, Colombia. METHODS: An observational retrospective study about dengue cases treated in adult ICU was conducted, in the Fundación Valle del Lili. We included cases between 2001 to 2015 years. Clinical data were collected from the ICU database and medical charts. A Cochran-Armitage test for trend was used to assess the presence of an association between fatal cases and total cases in dengue patients at ICU during the study period, and to evaluate differences in the mortality cases before and after the implementation of the dengue CPG. RESULTS: A total of 49,962 episodes of attention in ICU were analyzed, and 70 cases with severe dengue and dengue shock attended in ICU were included. The median age was 42 years (IQR = 24–60), eight cases were older than 65 years, and 54% were male. Five fatal cases were reported during this period. The fatal cases had a length of stay in ICU of 2 days (IQR = 1–4) vs. 2 days (IQR = 1–3) for nonfatal cases. Overall mortality for dengue cases in the ICU was 7.14%. The highest mortality was presented in 2007 with 33.33% (1/3), and after 2010 there were no fatal cases. Dengue mortality showed a decreasing linear variation over time in the ICU (p = 0.047); also there was a statistically significant difference over time in adults mortality before and after of implementation of dengue CPG (P = 0.029). CONCLUSION: Dengue mortality cases in the ICU have decreased in the last 15 years, which is related to early admission to the ICU and continuous clinical monitoring. [Image: see text] DISCLOSURES: All authors: No reported disclosures.